Pengaruh Disiplin Terhadap Prestasi Kerja Karyawan Pada PT PLN (Persero) Unit Induk Wilayah (UIW) Nusa Tenggara Barat UP3 Bima - Fathul Aziz; Mistar Mistar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Based on knowing how much the influence of discipline on employee performance at PT. PLN (Persero) West Nusa Tenggara Regional Master Unit (UIW) West Nusa Tenggara UP3 Bima, researchers used a descriptive method, which is a method of examining the status of a human group or an object, a system of thought or class of events in the present. From the research results of the questionnaire that was distributed to 47 employees of PT. PLN (Persero) Regional Main Unit (UIW) West Nusa Tenggara UP3 Bima, Discipline variable has a significant effect on Job Performance. This is indicated by the results of the calculation of hypothesis testing, it can be seen that tcount = 3.893 is greater than ttable = 2.01410 this means Ho is rejected and Ha is accepted, then there is a disciplinary influence on employee performance at PT. PLN (Persero) Regional Parent Unit (UIW). From the value of correlation or relationship (R) that is equal to 0.502. From the output obtained a coefficient of determination (R Square) of 0.252, which implies that the influence of the independent variable (Discipline) on the dependent variable (Job Performance) is 25.20% and the remaining 74.80% is influenced by other factors not yet examined such as work environment, motivation, compensation, training and others